Relating canopy size of pecan (Carya illinoinensis (Wagenh.) K. Koch) trees to transpiration - Taylor, Nicolette Jane (University of Pretoria, 2023)
Dissertation (MSc (Agric) Horticulture)--University of Pretoria, 2022.